The Effect of Using English Song Media toward Students’ Speaking Skills: English - M, Hilmy Hidayatullah Hilmy; Ukhtul Iffah; Nuril Firdaus; Uvil Nurizqiyanti (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2024)
This study aimed to analyze the impact of using pop song media on students' speaking skills. The method used was a quasi-experiment. This study was conducted in the tenth grade at SMAN 2 Situbondo. The sample was selected using the Slovin formula, which consisted of at least 44 students, so the researchers took 72 students divided into two classes: 36 students for the experimental class and 36 students for the control class. The experimental class was taught using pop song media, and controlled classes were taught by listening to the teacher's explanation of textbook material and doing assignments. The research instruments used the pre-test and post-test. The results of the research shown the difference between the two classes in the post-test mean score, where the experimental classes taught using pop song media scored higher than the control class taught using conventional media. The findings of this study lead to the conclusion that using pop song media is more effective on students speaking skills in the tenth grade at SMAN 2 Situbondo. It's based on the statistical hypothesis p-value, or sig (2-tailed) = 0.000 which was lower than sig α 0.05. It can be concluded that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) is accepted. Thus, it was proven that pop song media was effective on students' speaking skills at tenth grade in SMAN 2 Situbondo compared to students who use conventional media. So that the use of pop song media has a significant effect on students' speaking skills.